Adolescents’ Risk of Different Sexual Orientation Tendency in Terms of Family Factors (Case Study in Padang and Agam Regency) - Fajria, Lili; Irawati, Nuzulia; Malini, Hema; Mudjiran, Mudjiran; Refnandes, Randi (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: In the transition period, in adolescents occur the process of physical, cognitive, and social maturation. This period is essential in the formation of sexual identity, which related to gender and sexual orientation. Improper sexual identities will provoke sexual behavior problems. The problems with sexual behavior begin from differences in sexual orientation with a sexual orientation generally accepted by the public (heterosexual). In some adolescents, there is a change in sexual orientation that leads to homosexuality. The factors that play a significant role in adolescent sexual orientation are parenting. AIM: This study aimed to examine the risk of different sexual orientation tendencies in adolescents and the families’ factors in West Sumatra. MATERIALS AND METHODS: This study’s design was a cross-sectional study with 532 adolescents aged 13–18 years old as the respondents. It took 3 months to research by using a questionnaire as the instrument. The questionnaire’s data were analyzed using Chi-square. RESULTS: The results showed that the risk of different sexual behaviors in adolescents was 59.4% normal tendency, 26.7% low tendency, and 13.9% high tendency. Furthermore, family factors related significantly to the risk of different sexual behavior tendencies were gender and family intimacy factors (p < 0.05), while age, family type factors, and family income factors (p > 0.05) are not significantly related. CONCLUSION: Based on that, it concluded that the parents expected to develop closer relationships with family members.